2021
DOI: 10.1001/jamapediatrics.2021.2061
|View full text |Cite
|
Sign up to set email alerts
|

Experiences and Perspectives of Transgender Youths in Accessing Health Care

Abstract: ransgender and nonbinary people make up around 0.5% of the world's population (25 million people), and most are children, adolescents, and young adults. 1,2 A detailed list of transgender-associated terms and definitions is presented in eTable 1 in the Supplement. Transgender and nonbinary youths face considerable disparities in access to health care and outcomes. 1,[3][4][5][6] They are exposed to stigma and violence, 1 have an increased risk of anxiety and depression, and are more than 20 times more likely t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(41 citation statements)
references
References 114 publications
0
39
0
1
Order By: Relevance
“…The systematic review employed to explore the lived experiences of transgender and non-binary youths discovered six themes: internalising intense fear of consequences, experiencing prejudice undermining help-seeking efforts, experiencing pervasive stigma and discrimination in healthcare, traversing risks to overcome systemic barriers to transitioning, feeling vulnerable and uncertain in decision-making, and experiencing strengthened gender identity and finding allies 1. The review revealed that the youths reluctantly engaged in harmful practices to avoid seeking help from healthcare providers and agencies whom they perceived to have prejudicial beliefs against the health needs of the transgender community.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The systematic review employed to explore the lived experiences of transgender and non-binary youths discovered six themes: internalising intense fear of consequences, experiencing prejudice undermining help-seeking efforts, experiencing pervasive stigma and discrimination in healthcare, traversing risks to overcome systemic barriers to transitioning, feeling vulnerable and uncertain in decision-making, and experiencing strengthened gender identity and finding allies 1. The review revealed that the youths reluctantly engaged in harmful practices to avoid seeking help from healthcare providers and agencies whom they perceived to have prejudicial beliefs against the health needs of the transgender community.…”
Section: Resultsmentioning
confidence: 99%
“…The researchers conducted a systemic review which analysed high-risk practices in the transgender youth community due to fear of discrimination from healthcare professionals when seeking care. Selection criteria, data sources and searches, appraisal of transparency of reporting and data analysis were used to conduct the research study 1…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite its known benefits, access to these services in the Philippines 10 and elsewhere 11 , 12 has been limited and hindered by barriers. In the Philippines, barriers include the previous direct and vicarious experiences of stigma and discrimination, services remaining within spaces intended for HIV and cisgender men who have sex with men, and the absence of local guidelines or programs.…”
Section: Introductionmentioning
confidence: 99%